2018
DOI: 10.1155/2018/2087693
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Epidemiology of Methicillin-ResistantStaphylococcus aureusin a Tertiary Care Hospital in Moshi, Tanzania, as Determined by Whole Genome Sequencing

Abstract: Objective To determine molecular epidemiology of methicillin-resistant S. aureus in Tanzania using whole genome sequencing. Methods DNA from 33 Staphylococcus species was recovered from subcultured archived Staphylococcus isolates. Whole genome sequencing was performed on Illumina Miseq using paired-end 2 × 250 bp protocol. Raw sequence data were analyzed using online tools. Results Full susceptibility to vancomycin and chloramphenicol was observed. Thirteen isolates (43.3%) resisted cefoxitin and other antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
3
13
0
1
Order By: Relevance
“…National data from 9 African countries shows MRSA rates to approximate between 12 and 80%, with some countries exceeding 82% [6, 8]. For example, in East Africa, high prevalence rates of between 31.5 to 42% among patients and healthcare workers have been recorded in Uganda [9, 10], 31 to 82% MRSA prevalence in Rwanda [11, 12], and in 10 to 50% in Tanzanian studies [1321]. However, there have been some pockets of positive reports owing to antimicrobial stewardship and infection control practices such as South Africa, which recorded a modest decline from 34 to 28% since 2011 [6, 8, 22].…”
Section: Introductionmentioning
confidence: 99%
“…National data from 9 African countries shows MRSA rates to approximate between 12 and 80%, with some countries exceeding 82% [6, 8]. For example, in East Africa, high prevalence rates of between 31.5 to 42% among patients and healthcare workers have been recorded in Uganda [9, 10], 31 to 82% MRSA prevalence in Rwanda [11, 12], and in 10 to 50% in Tanzanian studies [1321]. However, there have been some pockets of positive reports owing to antimicrobial stewardship and infection control practices such as South Africa, which recorded a modest decline from 34 to 28% since 2011 [6, 8, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in East Africa have reported considerable genetic diversity and differences in sequence types of AMR genes particularly for ESBL (Table 2 , Fig. 1 ), MRSA (Table 3 ) [ 71 75 ], and CAR (Table 4 ). These are attributed to evolutionary events, including mutations, selection and gene transfer, in the AMR genes in MRSA, ESBL and carbapenem isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Further, a cross sectional study in Kenya, reported predominance of SCCmec type V followed by SCCmecII genes in healthy students residing within the university residence halls [83]. Several sequence types (STs) of MRSA have been reported in East Africa [71,74,75,77]. For instance, the ST88 and ST1797 have been reported to be the predominant sequence types causing wound infection and abscesses in clinical isolates in a tertiary hospital in Tanzania [74].…”
Section: Genetic Diversity Clinical Relevance and Regional Surveillamentioning
confidence: 99%
See 1 more Smart Citation
“…Микроорганизмы Staphylococcus aureus не случайно получили характеристику «двуликого Януса» [5], так как, представляя собой оппортунистические патогены, могут вызвать инфекционный процесс с тяжелым инвазивным течением. Так, открытые в 1961 году штаммы бактерий Staphylococcus aureus, резистентные к действию метициллина (methicillin-resistant Staphylococcus aureus -MRSA) [15], являются ведущей причиной тяжелых нозокомиальных инфекций в странах всего мира [18]. Особенно высокий риск развития MRSAассоциированных инфекций отмечается у недоношенных и новорожденных детей с очень низкой массой тела [43], для которых характерен низкий уровень экспрессии образраспознающих рецепторов [1].…”
Section: Introductionunclassified